Circularly polarized wave beamforming using one‐dimensional Fresnel zone plate. Issue 5 (28th January 2019) - Youn, Youngno; Hong, Wonbin
Abstract: This letter entails a methodology to steer circularly polarized (CP) wave main beam in the near‐field region. The letter first demonstrates a planar circular polarizer which can convert an incoming linearly polarized wave into a CP wave from 24.0 to 40.0 GHz. Afterwards a one‐dimensional Fresnel zone plate consisting of electrically opaque and transparent regions is devised to formulate constructive interference for CP near‐field beamsteering at 22°. Measurement ascertains that the axial ratio and TE/TM phase difference at the aforementioned angle is 0.36 dB and 87.1°.